PENGARUH IBADAH PERJAMUAN KUDUS TERHADAP PERTUMBUHAN KEROHANIAN JEMAAT GMAHK BUNSADAN KOTA MARUDU SABAH, MALAYSIA BERDASARKAN 1 KORINTUS 11:27 - Hitlor, Enos; Hendriks, Alvyn C. (Fakultas Filsafat Universitas Advent Indonesia, 2020)
In writing this thesis, the author tries to examine the effect of the Holy Communionservice on the spiritual growth of the GMAHK Bunsadan Kota Marudu Sabah Cityof Malaysia congregation based on 1 Corinthians 11:27. This research is based onfour indicators: The theological understanding of the word